Impact of Intensive Case Management on Child Welfare System Involvement for Substance-Dependent Parenting Women on Public Assistance - Dauber, Sarah (2012)
This study examined the impact of intensive case management (ICM) on decreasing child welfare system involvement in a sample of substance-dependent parenting women who participated in a welfare demonstration study comparing ICM to usual screen-and-refer models employed in welfare settings. Previous research established the effectiveness of ICM in both increasing engagement in substance abuse treatment and in promoting abstinence, and the current study tested whether ICM had downstream impacts on child welfare outcomes not directly targeted by the intervention. The sample included 302 mothers recruited from welfare offices and their 888 minor children. Child welfare outcomes were available from administrative records for four years following study entry and included incident reports and out-of-home child placements. An initial positive effect of ICM was found on child placements, but its impact lessened over time and was likely due to the increased contact with case managers that occurred early in the study. Overall, minimal benefits of ICM were found, suggesting that while ICM was effective in the areas of treatment engagement and abstinence, there were no downstream benefits for child welfare outcomes. Implications of findings in terms of increased need for cross-system collaboration are discussed.